STUDENTS’ PERCEPTIONS ON WEB-BASED LANGUAGE LEARNING USE FOR TOEFL INSTRUCTION AT UNIVERSITAS RIAU - Radipta, Muhammad Aulia; Daud, Afrianto; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to explore the perceptions of English Study Programstudents towards web-based learning for TOEFL instruction at the Universitas Riau.The population of this study consists of second-year students, totaling 117 participants.The researcher used a questionnaire comprising 15 questions to gauge the students'perceptions. The questionnaire included two indicators: implementing and benefits ofweb-based language learning. The results revealed that students' perceptions of TOEFLinstruction via web-based learning were predominantly positive. The overall perceptionpercentage was 77.61%, which is classified as a positive perception. This indicates thatthe majority of students find web-based learning for TOEFL instruction beneficial.Key Words: Perception, Online Learning, TOEFL